Cavβ surface charged residues contribute to the regulation of neuronal calcium channels - Tran-Van-Minh, Alexandra; De Waard, Michel; Weiss, Norbert (Molecular brain, 2022)
Voltage-gated calcium channels are essential regulators of brain function where they support depolarization-induced calcium entry into neurons. They consist of a pore-forming subunit (Cavα1) that requires co-assembly with ancillary subunits to ensure proper functioning of the channel. Among these ancillary subunits, the Cavβ plays an essential role in regulating surface expression and gating of the channels. This regulation requires the direct binding of Cavβ onto Cavα1 and is mediated by the alpha interacting domain (AID) within the Cavα1 subunit and the α binding pocket (ABP) within the Cavβ subunit. However, additional interactions between Cavα1 and Cavβ have been proposed. In this study, we analyzed the importance of Cavβ3 surface charged residues in the regulation of Cav2.1 channels. Using alanine-scanning mutagenesis combined with electrophysiological recordings we identified several amino acids within the Cavβ3 subunit that contribute to the gating of the channel. These findings add to the notion that additional contacts besides the main AID/ABP interaction may occur to fine-tune the expression and properties of the channel.
Keywords: Calcium Channels; Calcium; vápníkové kanály; vápník; Neurons; neurony